(+2) + (+4) =
(-3) + (+7) =
(-2) + (-4) =
(+2) + (-5)=
3+5=
(-2)+(-8)=
2+(-8)=
(-3)+10=
A= (-3,8) + 15 + 5,8 + (+2) + (-5)
A=
A=
A=

2
a=(+2)+(4)=6 b= -3 + (+7) = 4 c= -2+(-4) = -6 d = 3+5=8 e= -2+(-8) = -10 f = 2 +(-8) = -6 g = -3+10 = 7 h = -3.5-5+15+5.8+2 = 14.3

Réponses

2014-04-18T22:24:12+02:00
A. 6
b. 4
c. -6
d. -3
e. 8
f. -10
g. -6
h. 7
A = -3.8 +20.8 +2 -5
A= -8.8 + 22.8 
A = 14
2014-04-18T22:45:17+02:00

(+2) + (+4)

= 2 + 4

= 6


 (-3) + (+7) 

= -3 + 7

= 4


 (-2) + (-4)

= -2 - 4

= -6


 (+2) + (-5)

= 2 - 5

= -3


3+5

= 8


(-2)+(-8)

= -2 - 8

= -10


 2+(-8)

2 - 8

= -6


 (-3)+10

-3 + 10

= 7


A= (-3,8) + 15 + 5,8 + (+2) + (-5)

A= -3,8 + 15 + 5,8 + 2 - 5

A= -3,8 + 5,8 + 15 + 2 - 5

A= 2 + 17 - 5

A= 19 - 5

A= 14